UNMANNED AERIAL VEHICLE DERIVED 3D MODEL EVALUATION BASED ON ICESAT-2 FOR ICE SURFACE MICRO-TOPOGRAPHY ANALYSIS IN EAST ANTARCTICA - Y. He; G. Qiao; H. Li; X. Yuan; Y. Li (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
Modelling of ice sheet micro-topography based on Unmanned Aerial Vehicle (UAV) is meaningful for the understanding of interactions between local ice mass and climate. 3D reconstruction based on UAV has advantages that satellite remote sensing cannot replace. Here, the surface micro-topography measurement was performed during the China's 36th Antarctic expedition (CHINARE) in 2019–2020, using an UAV platform composed of a DJI Phantom 4 and a D-RTK GNSS mobile station around Zhongshan Station of China. Then, four partly overlapped models were obtained by the SfM-MVS technology. Affected by the complex environment factors, the performance of this technology sometimes is challenged over the marginal Antarctic Ice Sheet. Satellite altimetry is one of the most essential technologies for land ice surface elevation measurements, widely used in regional or global ice mass balance estimations.We use the land ice surface heights with high accuracy derived from the Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2) to compare with the UAV-derived models. Combined with the high precision and space-time resolution of ICESat-2 satellite altimetry, the results of the model were evaluated under different terrain conditions. It has been certified that the derived models without extra GCPs were capable of detecting the surface micro-topographic features if considering the potential factors, which can be popularized and developed in polar research.